Identifikasi Kebisingan Lalu Lintas Pada Jalan Tamalanrea Raya Di Kota Makassar - Rachmat Ramadhan; Natsir Abduh; Nurhadijah Yunianti (Jurnal Penelitian Teknik Sipil Konsolidasi, 2026)
One form of noise that can affect human health is traffic noise caused by vehicles. The residential area of Bumi Tamalanrea Permai in Makassar is a densely trafficked area, resulting  noise along the streets. This study aims to determine the level of noise and the best mathematical modeling to predict the noise level in the residential area. The type of research used is quantitative method where data analysis and mathematical modeling using multiple linear regression with Statistical Package for the Social Sciences (SPSS) software. In this study, the measurement results of noise have exceeded the threshold in the residential area were found to be 55 (dB). In the measurement at point I, the highest average noise measurement result is 81.89 (dB) while at point II, the highest measurement is 76.77 (dB)). The best mathematical modeling found using the Stepwise method at 5 meters is: Y = 35.925 + 0.018X1, + 0.691X4 + 0.226X3 + 0.030X2, while at 10 meters is: Y = 39.912 + 0.015X1 + 0.531X4 + 0.252X3 + 0.037X2.